Le palmier à huile - Jacquemard, Jean-Charles (éditions Quae, 2011)
Palm oil, extracted from the pulp of oil palm fruit, is the main source of vegetable fats and oils on the world market. Its ability to adapt to different climates and its productivity make it a major food safety component in Asian countries and the tropical belt. The book seeks to give the practitioner the necessary elements for setting up and operating a palm stand by combining the basic scientific and technical knowledge required to understand technical choices with the sustainable development priorities of the crop. Special mention is therefore made of actions to limit the potentially negative aspects and highlight the positive aspects of proposed techniques and strategies without forgetting efficient protection of people working in the plantations. Lastly, the essential factual components are given in terms of the use of oil palm products and their impact on human health.